411 Ovarian conservation in premenopausal women with early stage endometrial cancer. (18th September 2019) - Kaabia, O; Rym, Z; Nourallah, G; Aymen, L; Aymen, S; Mohamed, B; Hédi, K
Abstract : Objectives: To compare the overall (OS) and disease free (DFS) in young women with early-stage endometrial cancer undergoing hysterectomy with and without ovarian conservation. Methods: We conducted a a retrospective study of a prospective mono-centric database. We identified all premenopausal women under 50 years of age with stage I endometrioid adenocarcinoma of the endometrium who underwent hysterectomy from 2008 to 2018. Patients were stratified based on whether they underwent oophorectomy or had ovarian conservation. Results: The cohort of 20 women included 5 (25%) who had ovarian conservation and 15 (75%) who underwent oophorectomy. The rate of ovarian conservation was lower during the last decade. There were no statistical difference between the ovarian conservation group and the oophorectomy group in OS and DFS, in a Kaplan-Meier analysis, (respectively, P=0.073 and P=0.200). Conclusions: Ovarian conservation does not adversely affect survival for women with early-stage endometrial cancer.